Vanadium mineralization at Los Chihuidos sediment-hosted Cu–V deposit, Neuquén Basin, Argentina: An approach to vanadium ore forming processes - Rainoldi, Ana Laura (2023)
Vanadium mineralization at Los Chihuidos deposit of the Neuquén Basin is linked to the development of a redox front system related to the inflow of hydrocarbons into the red sandstone of the Huincul Formation. Interaction of hydrocarbons with oxidized red beds and connate water generated redox reactions where hematite was dissolved due to iron reduction resulting in the discoloration of the red strata. At the contact between oxidized red sandstone and reduced white sandstone, precipitation of specific mineral phases resulted in the V ore with minor amounts of Cu. With the implementation of the redox interface, abundant V-montmorillonite and V-hematite precipitated at the more oxidizing conditions and Cu-V-corrensite-type at the more reducing conditions of the redox front. As the redox front advanced with fluids constantly migrating into the reservoir, more reducing conditions were stablished, promoting chloritization and minor illitization with V-Cu incorporation and continuous upgrading of the ore. Main ore mineralogy consists of clay minerals including V-bearing montmorillonite, Cu-V-corrensite-type, V-di-trioctahedral chlorite and Cu-tri-trioctahedral chlorite with minor V-illite–smectite mixed-layer minerals and associated secondary V-hematite. Chloritization over illitization was favored due to high amounts of Fe and Mg in detrital clasts and in connate fluids and by low K availability related to low amounts of detrital K-feldspar. The spatial transition of V and /or Cu bearing clay minerals observed through the mineralized redox front at Los Chihuidos deposit (kaolinite → smectite → illite/smectite → corrensite-type → di- trioctahedral -chlorite → tri- trioctahedral -chlorite) and the related variation of V–Cu concentrations in bulk rock are indicative of increasing pH and decreasing Eh of resident solutions from red to white sandstones during the hypogene mineralization process. Late influx of Cu-rich oxidized basinal brines precipitated main copper ore with Cu-sulfides in the white sandstone up to the contact with the redox front in contact with hydrocarbons. During uplift and exhumation, percolation of meteoric water promoted remobilization of V and Cu and the precipitation of oxidized V–Cu ore.